Using serious mobile games to improve health literacy in rural Sub-Saharan Africa: A literature review - (:unkn) unknown (My University, 2022)
The African gaming industry is beginning to flourish as a result of a rise in the availability of inexpensive phones and the number of mobile phone subscribers. It has enabled the development and implementation of mobile serious games to promote healthy behavior change in rural communities. This paper examines the use of mobile serious games in healthcare education, with a particular focus on those designed to increase health literacy in rural Africa. Identifying and addressing the design challenges and issues faced by people living in rural African communities through the use of persuasive mobile games can promote behavior change among these underserved communities. We used PubMed, Scopus, Google Scholar and manual search to identify relevant studies published from 2011 to July 2021. The literature review highlights how the identified challenges affect the implementation of persuasive strategies, suggests design solutions for overcoming them, and discusses how persuasive games can be tailored to suit the target rural African populations. Some of the identified challenges are technical in nature (e.g., access to electricity and internet connectivity), while others are not (e.g., language diversity and low literacy). As the number of serious games for healthcare education and awareness continues to increase, it is essential for the successful implementation of inclusive mobile health technologies in rural Africa to identify and address the specific challenges faced by underserved populations such as rural African communities.
Keywords: African Research